Reviews - Popp, Veronica and Hardman, Elliot (Journal of Fandom Studies, The, 2015)
Abstract Time on TV: Temporal Displacement and Mashup Television, Paul Booth (2012) New York: Peter Lang Publishers, 255 pp., ISBN: 978-1433115691, p/bk, $39.95 The Ashgat e Resear ch Companion to Fan Cultures, Kinda Duits, Koos Zwaan, and Stijn Reinders (2014) Surrey, England: Ashgate Publishing Limited, 306 pp., ISBN: 9781409455622, h/bk, $149.95
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTM4Ni9qZnMuMy4zLjMyNV81